A cryptographic data hiding algorithm with high cover text capacity. (25th January 2019) - Azeem, Muhammad; He, Jingsha; Rana, Khurram Gulzar; Akhtar, Faheem
Cryptography and steganography are foremost techniques used to ensure security and confidentiality of secret information. In steganography, data hiding capacity with security is a great challenge for the researchers. In present scheme, a novel approach with combination of steganography and cryptography is proposed to achieve high data hiding capacity with greater security. To accomplish this goal, three level encryption is applied to hide secret message by using bit complement and bit right rotation. Different Unicode characters such as zero width non-joiner (ZWNJ), zero width joiner (ZWJ) and zero width character (ZWC), are used to conceal secret information into English cover text. To embed secret data into cover text, firstly, algorithm implements three level encryption on confidential data and then resulting binary is embedded into cover text by using Unicode characters. The results revealed that recently designed algorithm has higher data security due to light weight and efficient encryption mechanism along with 2-bit/char cover text capacity. Moreover, there is no overhead of secret key generation and exchange from source to destination. Projected technique is easy to implement, hard to break and reduces intruder's attention.